2010
DOI: 10.1080/19416521003732362
|View full text |Cite
|
Sign up to set email alerts
|

The Social Lives of Products:Analyzing Product Demography for Management Theory and Practice

Abstract: . (2010) 'The social lives of products : analyzing product demography for management theory and practice.', Academy of management annals., 4 . pp. 157-203. Further information on publisher's website:http://dx.doi.org/10. 1080/19416521003732362 Publisher's copyright statement:This is an electronic version of an article published in Carroll, G.R. and Khessina, O. and McKendrick, D.G. (2010) 'The social lives of products : analyzing product demography for management theory and practice.', Academy of mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Likewise, the production of certain types of Scotch whiskey, specifically, single malt whiskey, connotes a set of organizational codes based on opposition to mass production, support of localness, and distinctive and assertive flavor profiles that can be traced back to the unique regions or distilleries that produce them (McKendrick & Hannan, 2014). Indeed, products themselves often serve as touchstones not only for the values and standards of organizations but also for the broader evolution of the industries and product categories that emerge (Carroll, Khessina, & McKendrick, 2010; Khessina & Carroll, 2008).…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%
“…Likewise, the production of certain types of Scotch whiskey, specifically, single malt whiskey, connotes a set of organizational codes based on opposition to mass production, support of localness, and distinctive and assertive flavor profiles that can be traced back to the unique regions or distilleries that produce them (McKendrick & Hannan, 2014). Indeed, products themselves often serve as touchstones not only for the values and standards of organizations but also for the broader evolution of the industries and product categories that emerge (Carroll, Khessina, & McKendrick, 2010; Khessina & Carroll, 2008).…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%
“…Typical products usually enjoy advantages in exchanges, because they are easier for audiences to recognize and understand. Typicality allows audiences to establish criteria of legitimacy and merit, thereby enabling search, appraisal, and selection among products (Carroll et al, 2010). By conforming to categorical codes, producers can also signal their capability and commitment, which often results in favorable audience evaluation (Hsu et al, 2009).…”
Section: Categories and Typicalitymentioning
confidence: 99%
“…Cross-country exchanges deserve attention because countries usually differ in defining what is typical and what is not (Bourdieu, 1984; Carroll et al, 2010). Countries tend to specialize and develop along their unique paths (Reinecke et al, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Product price. We also included a few product-level control variables (Carroll et al, 2010). We included product price, adjusted for inflation rate, as a control variable because prior research has shown that product price affects the market performance of a product.…”
Section: Control Variablesmentioning
confidence: 99%
“…A product that is not a market success, therefore, can still provide a firm with important opportunities to acquire new knowledge and develop new capabilities (Wernerfelt, 1984). Although new product survival has been examined from many theoretical perspectives (Carroll, Khessina, & McKendrick, 2010), we still know very little about how capability stretching affects new product survival. We believe that examining the impact of capability stretching on new product survival may help us better understand the tension between product market performance and capability development and may also allow us to identify mechanisms through which firms manage this tension (Denrell & March, 2001;March, 1991;Wernerfelt).…”
mentioning
confidence: 99%